The many faces of a teacher - Gulane, Erlita T. (La Sallian research forum, 2011)
This qualitative study aimed at identifying the enduring good qualities of teachers which have significant impact on the lives of students. The respondents of this study were 66 fourth year Education students. The data gathered by a questionnaire, interviews and focused group discussions centered on the qualities of the respondents' best teachers and the ways their best teachers changed or influenced them. Findings pointed out to the importance of both personal and professional qualities of teachers in teaching in teaching their minds, in touching their hearts, and transforming their lives. Truly the teacher has many faces - the faces of a mother, a father, a sister, a brother, a motivator, and an inspiration, a friend a guide, a moral booster, a counselor, an idol, a healer, a role model, and even a tormentor. Some faces may appear ugly but underneath the surface of this face is the heart whose goal is to make difference in the lives of the students.